2011
DOI: 10.1186/1471-244x-11-43
|View full text |Cite
|
Sign up to set email alerts
|

The DUNDRUM-1 structured professional judgment for triage to appropriate levels of therapeutic security: retrospective-cohort validation study

Abstract: BackgroundThe assessment of those presenting to prison in-reach and court diversion services and those referred for admission to mental health services is a triage decision, allocating the patient to the appropriate level of therapeutic security. This is a critical clinical decision. We set out to improve on unstructured clinical judgement. We collated qualitative information and devised an 11 item structured professional judgment instrument for this purpose then tested for validity.MethodsAll those assessed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 17 publications
3
80
1
Order By: Relevance
“…De Vries Robbé et al found that the use of the SAPROF can be helpful in formulating treatment goals, progressing through stages of treatment, planning the phasing of treatment and facilitating risk communication [46,47]. The DUNDRUM-3 and DUNDRUM-4 are intended to serve the same processes of treatment planning and measurement of treatment outcome in domains relevant to risk reduction and risk management and to provide transparency when reporting to mental health tribunals and boards [22-26]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…De Vries Robbé et al found that the use of the SAPROF can be helpful in formulating treatment goals, progressing through stages of treatment, planning the phasing of treatment and facilitating risk communication [46,47]. The DUNDRUM-3 and DUNDRUM-4 are intended to serve the same processes of treatment planning and measurement of treatment outcome in domains relevant to risk reduction and risk management and to provide transparency when reporting to mental health tribunals and boards [22-26]. …”
Section: Discussionmentioning
confidence: 99%
“…These have been shown to predict moves from more secure to less secure places, along with measures of risk [24] and they have been shown to predict conditional discharge from hospital to the community [25]. The DUNDRUM-1 triage security instrument is a measure of the need for therapeutic security and is designed to be a static measure of a quality that is complementary to and distinct from risk of violence [26]. It has been shown to influence moves between levels of therapeutic security [24] and it is used also as a benchmark to enable comparisons between studies [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Validation studies have shown good psychometric qualities (Flynn, O'Neill, McInerney, & Kennedy, 2011;Freestone et al, 2015;O'Dwyer et al, 2011) and indicated that the DUNDRUM-1 items can predict the level of therapeutic security needed (Flynn et al, 2011;Freestone et al, 2015) and LOS (Davoren et al, 2015) while the DUNDRUM-3 and DUNDRUM-4 can predict moves between levels of therapeutic security (Davoren et al, 2012) and discharge (Davoren et al, 2013).…”
Section: Dangerousness Understanding Recovery and Urgency Manual (Thmentioning
confidence: 99%
“…The DUNDRUM toolkit is a suite of structured professional judgement instruments developed at the Central Mental Hospital Dundrum, Dublin, Ireland [1]. The toolkit is a set of instruments designed to assist clinical decision making when assessing the need for therapeutic security (DUNDRUM-1 triage security) [2] and urgency of need for therapeutic security (DUNDRUM-2 triage urgency) [3], assessing a patient's programme completion (DUNDRUM-3) and recovery (DUNDRUM-4) and therefore their ongoing need for security as well as a self rated instrument in which patients assess their own need for therapeutic security [1]. …”
Section: Introductionmentioning
confidence: 99%